Adverse childhood experiences, mental health, and social functioning: A scoping review of the literature. (May 2023) - Tzouvara, Vasiliki; Kupdere, Pinar; Wilson, Keiran; Matthews, Leah; Simpson, Alan; Foye, Una
Abstract: Background: Adverse childhood experiences (ACEs) negatively impact people's physical and mental health and social functioning. Research literature focuses on the impact of ACEs on physical and mental health, yet to our knowledge, no study has examined the literature on ACEs, mental health, and social functioning outcomes. Objective: To map how ACEs, mental health, and social functioning outcomes have been defined, assessed, and studied in the empirical literature and identify gaps in the current research which need further investigation. Methods: A scoping review methodology following a five-step framework was implemented. Four databases were searched CINAHL, Ovid (Medline, Embase) and PsycInfo. The analysis involved both numerical and a narrative synthesis in line with the framework. Results: Fifty-eight studies were included in the analysis, and three key issues were identified a) the limitations of research samples to date, b) the choice of outcome measures for ACEs, social and mental health outcomes, and c) the limitations of current study designs. Conclusion: The review demonstrates variability in the documentation of participant characteristics and inconsistencies in the definitions and applications of ACEs, social and mental health and related measurements. There is also a lack of longitudinal and experimental study designs, studies on severe mental illness, and studies including minority groups, adolescents, and older adults with mental health problems. Existing research is highly variable methodologically and limits our broader understanding of the relationships between ACEs, mental health, and social functioning outcomes. Future research should implement robust methodologies to provide evidence that could be used for developing evidence-based interventions.